Antibacterial Potential of Lactic Acid Bacteria Isolated from Cassava Tape Against Salmonella typhi - Ezra Eklesia; Hanasia Hanasia; Ravenalla Abdurrahman Al Hakim Sampurna Putra S; Oktaviani Naulita Turnip; Margaretha Yayu Indah Anugerahny (Biology, Medicine, & Natural Product Chemistry, 2026)
Lactic acid bacteria (LAB) from traditional fermented foods, such as cassava tape, are known to produce metabolic compounds with potential inhibitory effects against pathogenic bacteria. This study aimed to identify LAB isolated from cassava tape and to evaluate their antibacterial activity against Salmonella typhi (S. typhi). This research was a descriptive experimental study using cassava tape samples obtained from three traditional markets in Palangka Raya City. LAB isolation was performed on de Man Rogosa Sharpe Agar supplemented with 1% calcium carbonate (CaCO3), followed by macroscopic and microscopic observations and biochemical tests. Molecular identification was conducted using 16S rRNA gene analysis. Antibacterial activity against S. typhi ATCC 14028 was evaluated using the disk diffusion method on Mueller-Hinton agar. Three isolates were successfully obtained and coded as S1, S2, and S3. Molecular identification revealed that isolates S1 and S3 were identified as Limosilactobacillus fermentum, whereas isolate S2 was identified as Myroides phaeus and classified as a non-LAB. Antibacterial activity assays showed that none of the isolates produced inhibition zones against S. typhi at all tested concentrations. These results indicate that cassava tape contains LAB dominated by L. fermentum; however, under the experimental conditions of this study, the isolates did not exhibit antibacterial activity against S. typhi.